PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN NASABAH TABUNGAN (Studi pada Nasabah Taplus Bank BNI Cabang Ngaliyan) (Students' Journal of Economic and Management, 2016)
This study aimed to analyze the influence of the quality of service and product quality to customer satisfaction Taplus savings in Bank BNI Cabang Ngaliyan. The population in this study were all clients Taplus Savings in Bank BNI Ngaliyan in 2016 as many as 155 people. Based on the formula Slovin obtained a sample of 100 people. The samples in this study using purposive sampling, that the sampling technique based on the criteria of customer savings Taplus are still active and have become customers of more than 1 year. The analysis tool used is the test valididtas, reliability and multiple linear regression analysis. The results of the analysis can be concluded that: the quality of service a positive effect on customer satisfaction. Product quality positively affects customer satisfaction. Keywords: quality of service, product quality and customer satisfaction